THEORETICAL AND LEGAL FOUNDATIONS OF LEGAL COMMUNICATION OF THE JUDICIARY - Макеєва, Олена Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: the theoretical and legal foundations of legal communication of the judiciary are studied in the article. The principles of publicity and openness of justice are analyzed. Research methods: general scientific, historical, sociological, statistical, and comparative methods are used in the work. Results: the concept of legal communication of the judiciary, its forms and methods have been clarified. It is concluded that the legal communication of the judiciary is an important factor in implementing the principle of publicity and openness of justice, increasing the level of public confidence in the court under the conditions of the information and legal society. Discussion: finding ways to improve legal communication of the judiciary. Legal communication of the judiciary is a set of processes and forms, using the appropriate means provided by the subjects of the judiciary for the proper performance of the tasks and powers of the courts, implementation of the principles of openness and publicity of the judicial process, public confidence in the judicial system. Forms of legal communication of the judiciary: a) an information one, which is conditioned by the right of citizens to receive information on the content of the activity of the bodies of the judiciary; b) a procedural one, which is directly related to the broadcasting of the judicial processes; c) an organizational one, which provides for the implementation of various court-organized activities, which increases the level of communication of the court with other social institutions and citizens; d) an electronic one, which significantly simplifies the court's interaction with users of court services. Methods of legal communication of the judiciary: maintaining its own website / web portal, social networking, interviews with court staff; communication with journalists, organization of educational events, open days by courts, broadcasting of judicial processes by technical means of courts, organization of work of the court communication team.